Candidate Gene of Milk Protein for Genetic Improvement of Dairy Cattle - Santiananda Arta Asmarasari; C Sumantri; A Gunawan; E Taufik; A Anggraeni (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
The objective of this paper is to explore some efforts to increase milk protein of dairy cows through a milk protein control gene selection approach. Improving the quality of cow's milk has shifted to increase milk protein levels, due to nutritional and economic interest. The breeding process in producing dairy cattle with the advantage of having high milk protein content is more effectively carried out by molecular biotechnology approaches. The content of cow's milk protein is controlled by cow's milk protein control genes. In the process to produce dairy cattle with the advantage of having high milk protein content, it can be done with a selection approach based on milk protein control genes, namely CSN1S1, CSN2, CSN1S2, and CSN3. Once known, the main controller gene that causes high levels of cow's milk protein, it will be easy to identify dairy cattle that have these advantages, so that the selection of dairy cattle can be done since at early age.